LAFARGA, Francisco (ed.) La traducción fragmentaria: su lugar en antologías y revistas (1898-1936). Madrid: Guillermo Escolar Editor. 2017. 224 pp. ISBN 978-84-17134-28-0. - Llopart Babot, Sandra (Hikma, 2018)
Reseña (sin resumen)